Susceptibility Weighted Imaging (SWI) Recommended as a Regular Magnetic Resonance Diagnosis for Vascular Dementia to Identify Independent Idiopathic Normal Pressure Hydrocephalus Before Ventriculo-Peritoneal (V-P) Shunt Treatment: A Case Study - Huang, Wen-Qing; Lin, Hui-Nuan; Lin, Qing; Tzeng, Chi-Meng (Frontiers in Neurology, 2019)
Idiopathic normal pressure hydrocephalus (INPH) with comorbid vascular dementia (VD) often have poor response to ventriculo-peritoneal (V-P) shunt. Here, three patients over the age of 60 came to the hospital with the similar clinical symptoms, Evan index over 0.3, mini-mental state examination (MMSE) score less than 27, and cerebrospinal fluid (CSF) pressure under 200 mmH2O. They accepted conventional brain imaging scanning, followed by magnetic resonance-susceptibility weighted imaging (MR-SWI) scanning. We found that MR-SWI could distinguish INPH from leukoaraiosis (LA) and cerebral amyloid angiopathy (CAA), through cerebral microbleed (CMB) images, sharply. We highly recommended incorporation of MR-SWI into INPH international guidance as a routine pre-operative diagnostic method preceding V-P shunt treatment.